Eating habits in judokas - Juříková, Jana; Nguyen, Hung Duc (Quality in Sport, 2018)
Purpose The aim of the paper was to find out eating habits of judokas from judo club in Holešov and students of programme Special Education of Security Bodies who practise combative sports including judo in University Campus in Brno-Bohunice. in the Czech Republic. Design/methodology/approach: The questionnaire survey was attended by 66 judokas in total, out of which there were 34 male (52%) and 32 female (48%) respondents. Women aged 20-25 years (average age in female group was 19.34), men also aged 20-25 years (average age in male group was 22.24). The questionnaire was anonymous. Research and practical limitations/implications: Majority of female respondents were students with non-sportive specialization, in men it is about a half (41% of respondents). Majority of respondents were practiced judo as a self - defense technique – this answer was given by 55.9% of men and 59.4% of women. 26.5% of men and 21.9% of women always pay attention to well-balanced diet. The highest number of respondents claims that they always respect specific need for energy income – 61.8% of men and 84.4 % of women. Merely 14.7% of men and 9.4% of women admitted that they do not consider specific energy income for sportspeople, and 61.8 % of men and 84.4% of women reported that they consider it sometimes. Respondents who use nutritional supplements mostly prefer carbohydrate-protein conjugates – this option was selected by 70.6% of men and 75% of women. Most respondents do not use supplements with vitamins and minerals – this answer was given by 64.7% of men and 75% of women. Originality/value: Most of respondents are interested in their nutrition. Many of them need some education from sports nutritionists.